USING CIRCUITS ON MINIMALIST PRESCHOOL LAND TO ASSIST WITH GROSS MOTOR PHYSICAL ACTIVITIES - Hariyanto Hariyanto; Miftahul Alimin; Mohammad Tohir (LP2M Universitas Ibrahimy, 2019)
The physical gross motor was the focus of this commitment. There are 37 percent minimalist schools in Malang. As a result, it is unable to conduct motor physical activities optimally. That difficulty was solved by implementing a circuit. To aid in the physical development of gross motor skills. Despite the fact that it was a minimalist school. Teachers can create circuits in their classrooms after receiving training. Material used in child-safe circuits. The material used can be saved. and used once more.